22q11.2 duplications: Expanding the clinical presentation. Issue 3 (29th November 2021) - Bartik, Lauren E.; Hughes, Susan S.; Tracy, Meghan; Feldt, M. Max; Zhang, Lei; Arganbright, Jill; Kaye, Alison
Abstract: 22q11.2 duplication syndrome has a frequency of ~1/700 in the intellectual disability population. Despite this frequency, there is limited information on the variable clinical presentation. Although the phenotype and incidence of congenital anomalies are well described for 22q11.2 deletion syndrome, they are not as well understood for individuals with 22q11.2 duplication syndrome. This study is a single‐center, retrospective review of patients diagnosed with 22q11.2 duplication syndrome designed to categorize the variable phenotype seen in these individuals. The data suggest that the incidence of congenital anomalies may be higher than previously reported for this syndrome. Affected individuals are at increased risk for a variety of problems including gastrointestinal complications, endocrine dysfunction, ophthalmologic abnormalities, palatal anomalies, congenital heart disease, musculoskeletal differences, and neurologic abnormalities. Individuals with 22q11.2 duplication syndrome would benefit from care coordinated by a multidisciplinary team and managed according to the 22q11.2 deletion syndrome guidelines.